A new species of frog of the genus Abavorana Oliver, Prendini, Kraus & Raxworthy 2015 (Anura: Ranidae) from Gunung Jerai, Kedah, northwestern Peninsular Malaysia - Quah, Evan S.h.; Anuar, Shahrulm.s.; Grismer, L.l.; Wood, Perry L. Jr.; Azizah, Siti M.n.; Muin, Mohd Abdul (Zootaxa, 2017)
The recently erected ranid genus Abavorana is thought to contain one nominal species, A. luctuosa, that ranges from the Thai-Malay Peninsula to Borneo and Sumatra. A melanistic form from Gunung Jerai, Peninsular Malaysia previously thought to be the same species is new to science and herein described based on new specimens and data. Based on morphology, colour pattern, and phylogenetic analyses using the mitochondrial genes 16s, ND1 and three tRNAs (tRNA-leu, tRNA-lle, and tRNA-gln), we determine that this new species, Abavorana nazgul sp. nov., is the sister lineage to other populations of A. lucutosa from Peninsular Malaysia and one from Borneo. It differs from A. luctuosa by a minimum sequence divergence of 7.5% and the following combination of morphological and colour pattern characteristics: (1) SVL 42.1–50.0 mm in adult males; (2) prominent but small humeral glands in males (2.3–2.5 mm); (3) dorsolateral stripe continuous, orange to yellow in colour; (4) mid-dorsal region of dorsum black, with or without faint orange or yellow speckles; (5) flanks with distinct cream spots; (6) dorsal surfaces of limbs with cream spots–bar; and (7) venter grayish brown, with prominent light spots on throat and belly. The discovery of yet another endemic species from the upland regions of Peninsular Malaysia highlights the rich diversity of these habitats and the need for more studies in montane areas throughout the region.